Daily distribution of meteor flight frequency according to radio observations - Useinov, B.M.; Solodovnik, A.A.; Sartin, S.A.; Nurakay, G.K. (Recent Contributions to Physics, 2023)
The paper considers the problem of studying the daily distribution of the passage of meteoroids by radio observation. The advantages of the chosen method of registration over the classical optical and photographic methods of observation are considered. A voluminous series of data was obtained using a registration facility implemented on the basis of the Center for Astrophysical Research at the North Kazakhstan University named after Manash Kozybayev. Processing, analysis and systematization of the obtained data on meteor phenomena have been carried out. Based on the obtained observational data, on the basis of the Center for Astrophysical Research at the North Kazakhstan University named after Manash Kozybayev, using the Multi VirAnalyzer program, namely the Date Recorder, the daily distribution of the meteor flight frequency was calculated. Also, with the help of the Microsoft Excel software application, diagrams of the daily distribution of the meteor passage frequency were constructed. During the analysis of the obtained diagrams of the daily distribution of the meteor passage frequency, the peak and average daily values of meteor activity were determined. Based on the daily distribution, diagrams of the frequency of meteor passages were constructed for certain months during which the Perseid and Leonid meteor showers are active. A clear correlation with the results of studies of other laboratories of a similar line of research is shown.